Endoscopic Retrograde Chola ngiop ancre atogr aphy in Pediatric Population: A Decade-Long Experience from 2 Tertiary Centers - Batıbay, Ersin; Yüksekyayla, Osman; Polat, Mahmut; Bayhan, İbrahim; Sevinç, Mehmet; Dağ, Ahmet; Barutçu, Sezgin; Kocaman, Osman Hakan; Boleken, Mehmet Emin; Şimşek, Cem; Erkmen, Fırat; Efe, Cumali (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Endoscopic retrograde chola ngiop ancre atogr aphy (ERCP) is an essential diagnostic and therapeutic method for pancreato-biliary disorders in adults, but its use in pediatric populations remains limited. This study aims to evaluate the indications, technical success, and safety of ERCP in pediatric patients. Materials and Methods: A retrospective analysis of all ERCP procedures performed on patients under 18 years of age was conducted at 2 tertiary centers in Türkiye (Harran University and Gaziantep University Hospital) during the period between January 2013 and May 2024. The data used for the study were obtained from patients’ medical records. Results: A total of 153 ERCP procedures were performed on 83 pediatric patients (64%, female) with a mean age of 12.9 years (range 3-17) at the time of ERCP. Common bile duct stones were the most frequent indication (n = 39, 47%) for ERCP, followed by biliary hydatid cyst-related complications (n = 24, 29%). The overall cannulation success rate was 98.7% (82/83). Endoscopic sphincterotomy was performed in 79 (95%) patients. More than one ERCP procedure was performed in 41 (49%) patients. Stones were extracted in 32 patients (30 were biliary and 2 pancreatic). Stent placement was performed in 33 patients (25 biliary and 8 pancreatic). Post-ERCP pancreatitis developed in 4.8% (n = 4) of patients, and all classified as mild. Ten (12%) patients developed mild/moderate cholangitis following ERCP. One patient (1.2%) experienced minor bleeding. About half of the patients (48%) were discharged within 1 day postprocedure. No patient experienced procedure-related mortality. Conclusion: Our study results indicate that ERCP is both effective and safe in the pediatric population. Cite this article as: Batıbay E, Yüksekyayla O, Polat M, et al. Endoscopic retrograde chola ngiop ancre atogr aphy in pediatric population: A decade-long experience from 2 tertiary centers. Turk J Gastroenterol. 2025;36(5):321-327